Intra- and interspecific ecophysiological responses to waterlogging stress in two contrasting waterlogging-tolerant arbor species - Tian, Mengjie; Li, Dadong; Cisse, El-Hadji Malick; Miao, Lingfeng; Zhou, Jingjing; Yang, Weizong; Chen, Boshen; Li, Lijun; Tian, Huimin; Ye, Bingbing; Yang, Fan (Frontiers in Plant Science, 2023)
At present, establishing planted forests, typically composed of not more than two tree species, to avoid forest losses has received increasing attention. In addition, investigating the impact of environmental stress such as waterlogging on different planting patterns is essential for improving wetland ecosystem resilience. Knowledge about the impact of waterlogging on planted forests is crucial for developing strategies to mitigate its adverse effects. Here, we conducted experimentally a simulated pure and mixed planting system composed of two contrasting WL-tolerant species (Cleistocalyx operculatus and Syzygium cumini) to determine their ecophysiological responses based on the type of interaction. Results showed that the aboveground growth performance of S. cumini was better than that of C. operculatus under well-watered conditions regardless of the planting model, which is contrary to the belowground accumulation that was significantly improved in C. operculatus. Intra- and interspecific interactions in different planting models facilitated the growth performance of C. operculatus while provoking a significant competition in S. cumini under waterlogging. Such phenomenon was explained through the remarkable ability of C. operculatus to naturally increase its root network under stress on non-stress conditions compared with S. cumini. In this study, two main factors are proposed to play key roles in the remarkable performance of C. operculatus compared with S. cumini following the planting model under waterlogging. The high level of nitrogen and phosphor absorption through C. operculatus primary roots and the significant starch biosynthesis constituted the key element that characterized the facilitation or competition within the intra- or interspecific interactions shown in C. operculatus compared with S. cumini. Furthermore, the intraspecific competition is more pronounced in S. cumini than in C. operculatus when grown in a pure planting pattern, particularly when subjected to waterlogging. However, when the two species are planted together, this competition is alleviated, resulting in enhanced waterlogging tolerance.